Tax pass-through in the European beer market - Aria Ardalan; Sebastian G. Kessing (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the pass-through of indirect taxes on beer prices in the European Union (EU). Exploiting the variation of value added tax rates, beer excise tax rates, and beer prices in a panel of monthly data from 1996 to 2016 of all current 28 EU member states, we estimate the tax pass-through of specific beer excise taxes and ad valorem value added taxes (VAT). VAT is under-shifted at a rate of approximately 70%. Specific excise taxes are almost fully shifted to prices in the EU, but, in contrast to the empirical findings for the US, there is no evidence of over-shifting. The difference between the two tax pass-through rates points towards the importance of imperfect competition in the European beer market. Excise tax increases are passed through faster and at a higher rate than excise tax decreases.
Keywords: H22; H23; 330; tax incidence; pass-through; VAT; excise taxes; EU; beer